Histologic study of the effect of laser therapy on bone repair - Diego Blaya (2008)
AIM: This study used histologic analysis and HE staining to evaluate laser biomodulation of bone repair in cavities made in the femurs of rats that underwent non-ablative laser irradiation. METHODS AND MATERIALS: Eighteen male Wistar rats weighing 300 to 400 grams were randomly assigned to three groups of six animals each. A surgical defect site was produced with a trephine about 2 mm in diameter under abundant irrigation. In Group I the complete surgical protocol to produce a bone defect was followed but without laser radiation (control). In Group II a continuous wave 830 nm infrared laser was used at 10 J/cm2 and 50 mW at each point of the surgical site. In Group III a continuous wave 685 nm infrared laser at 10J/cm2 and 35 mW was used at each point of surgical site. The animals were irradiated at intervals of 48 hours beginning immediately after the preparation of the defect and were sacrificed on the 15th, 21st, and 30th days. Slides were studied by means of descriptive analysis. RESULTS: Greater degrees of new bone formation and vertical regeneration were found in the irradiated groups than in the control group. CONCLUSION: Laser therapy in this study protocol was efficient in promoting bone repair. CLINICAL SIGNIFICANCE: The use of laser technology has been used to improve the clinical results of bone surgeries and to promote a more comfortable postoperative period and quicker healing.